The Structural Characteristics and Phase Transformation in Al2O3 Glass. A Molecular Dynamics Simulation - Thi Quynh Nhu, Tran; Huu Kien, Pham; Quang, Pham Dinh; Yen, Nguyen Hai; Huong, Vu Thi Thanh; Dung, Dao Ngoc; Trang, Giap Thi Thuy (VNU Journal of Science: Mathematics - Physics; Vol 38 No 2DO - 10.25073/2588-1124/vnumap.4663, 2022)
In this work, we have performed a simulation to study the structural characteristics and phase transformation in Al 2 O 3 glass under compression. The structural characteristics of Al 2 O 3 glass were examined via AlO x units, OAl y linkages, the average bond distance distributions, order parameters, and visualization of simulation data. The result showed that the network structure of Al 2 O 3 glass is built mainly by AlO x ( x = 3, 4, 5, 6, 7) units that are linked to each other via common O atoms. We found that the distribution of AlO x units in network structure is not uniform but tends to form clusters contained AlO x units. In addition, during a moderately long time, the glass has a two-phase that consists of separate low-density (LD) and high-density (HD) phases. The size of these phases significantly depends on the compression.